Keanekaragaman Dan Kelimpahan Makrozoobentos Di Ekosistem Mangrove Desa Persatuan Kabupaten Pohuwato Provinsi Gorontalo - Kadu, Sintia; Marini S. Hamidun; Chairunnisah J. Lamangantjo; Ramli Utina; Zuliyanto Zakaria; Regina Valintine Aydalina (CV. ULIL ALBAB CORP, 2024)
Macrozoobenthos is an animal species that lives on the bottom of the waters and has various roles in the ecosystem, such as its role as a biological indicator that reacts to the condition of water quality so that its existence can be used as an indicator of water quality. This study aims to determine the diversity and abundance of macrozoobenthos in the mangrove ecosystem of Persatuan Village, Pohuwato Regency. This type of research is quantitative descriptive, the data collection method uses a survey method and the determination of observation stations uses a purposive sampling technique. Sampling was carried out at 2 stations, namely station 1 muddy substrate type and station 2 sandy mud. Based on the Macrozoobenthos data obtained in the mangrove ecosystem of Persatuan Village, there are 22 species consisting of 15 families and 22 genera with a total of 5,363 individuals. The diversity of Macrozoobenthos at station 1 obtained a value of H '= 2.42 and station 2 with a value of H '= 1.51. The abundance at stations 1 and 2 has a high category. The high value of the Abundance index at station 1 and station 2 indicates the presence of a dominant species, namely the Telescopium mauritsi species. The Telescopium mauritsi species has the highest abundance at each station with an index value of Di = 0.311.